TRANSLATION APPLICATIONS IN EFL CLASSROOM: INSIGHTS FROM STUDENT PERCEPTIONS - Siumarlata, Viktor; Sallata, Yizrel Nani; Rachel (FKIP Unismuh Makassar, 2024)
With the advanced and innovative development of Information and Communication Technologies (ICT), translation apps have gained popularity. As a language learning tool, translation app has become increasingly popular among students, especially those who are learning a new language on their own. Learning a foreign language can be a challenging task, especially if you are not fluent in the language you are trying to learn. However, with the help of modern technology, translation apps can be one of the tools to help learn a new language. The objective of this research is to investigate the students’ perception on the use of translation applications. This study uses a qualitative method. Researchers applied this method to describe students’ perceptions about the use of translation apps in learning foreign languages. The results of this study indicate that the sixth semester srudents of English Education Study Program of UKI Toraja (Christian University of Indonesia Toraja) have 2 different perspectives in responding to the use of translation applications in learning foreign languages, namely positive and negative perspectives. From the positive perspective, mostly students stated that translation app in learning are really helpful in translating languages, increasing vocabulary, translation apps speed us up in translating languages, easy to use, and some of them are free. From negative perspective, most of the students stated that translation app can make them lazy to learn new things and become dependent, so there is no effort to try to increase knowledge